2021
DOI: 10.1186/s12909-021-03047-2
|View full text |Cite
|
Sign up to set email alerts
|

Application of online case-based learning in the teaching of clinical anesthesia for residents during the COVID-19 epidemic

Abstract: Objective COVID-19 prevention and control demand a reduction in crowd gathering, which has a significant impact on traditional teaching and offline case-based learning (CBL). In order to mitigate the impact of the COVID-19 outbreak on clinical teaching, we aimed to compare the effects of an online CBL with traditional teaching model on learning outcomes of anesthesia residents. Methods Residents rotated in the Department of Anesthesiology in Beijin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 29 publications
2
16
0
Order By: Relevance
“…Additionally, integration into Blackboard and having to motivate their findings helped integrate other areas of knowledge such as anatomy and physiology. This links well into the aims of CBL which are to discourage memorisation of theoretical knowledge and rather to encourage the practical application and integration of theoretical knowledge (Duan et al, 2021). The results also link into the findings by Whitfield et al (2021) that students using blended learning have more time to think about and grasp complex clinical concepts than they would have, had they only had in-class practical interactions and that they were able to build greater critical thinking and reasoning skills.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Additionally, integration into Blackboard and having to motivate their findings helped integrate other areas of knowledge such as anatomy and physiology. This links well into the aims of CBL which are to discourage memorisation of theoretical knowledge and rather to encourage the practical application and integration of theoretical knowledge (Duan et al, 2021). The results also link into the findings by Whitfield et al (2021) that students using blended learning have more time to think about and grasp complex clinical concepts than they would have, had they only had in-class practical interactions and that they were able to build greater critical thinking and reasoning skills.…”
Section: Discussionsupporting
confidence: 72%
“…CBL and vignettes have been suggested as substitutes for isolated case studies and are often used in healthcare education with the aim of preparing students for clinical practice by using realistic clinical scenarios (McLean, 2016). CBL takes clinical cases and uses these as a background to encourage students to think actively as medical experts (Duan, Li, Wang, Gao & Zhang, 2021). In addition, CBL vignettes should address present learning objectives, should be logical in flow and should be student-centred in design (Ma, Hubal & McLaughlin, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…However, the study on anesthesia case-based online learning reported higher satisfaction than conventional case-based learning [6].…”
Section: Introductionmentioning
confidence: 83%
“…Previous studies have shown that online learning has limitations in clinical and technical skill training [5]. Online case-based learning in the teaching of clinical anesthesia reported skill training limitations and showed a negative effect on students' attitudes [6].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation